Combined Antibacterial and Anticancer Potential of UK Medicinal Plant Extracts against Escherichia coli - Kaur, Navroop; Ralhan, Raghav (PSM Biological Research, 2026)
Medicinal plants have long served as important sources of therapeutic agents, especially for managing infectious diseases. The rising prevalence of antibiotic-resistant bacteria, particularly Gram-negative pathogens such as Escherichia coli, has intensified the search for alternative antimicrobial strategies. This study investigates the synergistic antibacterial activity of extracts from different parts of five medicinal plants—Cakile maritima (roots and seeds), Eucalyptus camaldulensis (leaves), Balanites aegyptiaca (leaves), Aegle marmelos (leaves), and Camellia sinensis (leaves)—against E. coli. These plants are traditionally used for medicinal purposes and contain diverse bioactive compounds, including phenolics, flavonoids, terpenes, saponins, and polyphenols, which may act together to enhance antimicrobial effects. The study focuses on combined plant extracts rather than individual ones, highlighting the synergy of phytochemicals as a promising approach to antimicrobial therapy. The documented results show that mixtures of extracts exhibited stronger inhibitory activity against E. coli than single extracts, suggesting cooperative interactions among their bioactive constituents. This finding is significant, as many plant extracts are less effective against Gram-negative bacteria when used alone. Considering that E. coli is a major cause of urinary tract infections, diarrhea, pneumonia, and other serious infections, these synergistic effects underline the therapeutic potential of plant combinations. The study supports the development of plant-based combinations as alternative or complementary antimicrobial agents, emphasizing the need for further research into their mechanisms, safety, and clinical applicability. Overall, these medicinal plants represent valuable natural resources for designing effective treatments against E. coli-associated infections, offering a promising strategy to combat antibiotic-resistant pathogens.